Differentiated disorders of the immune system in acute hematogenic and acute posttraumatic osteomyelitis in children - G. A. Chudilova; V. A. Tarakanov; E. A. Chicherev; Yu. V. Teterin; N. K. Barova; M. N. Mitropanova (Медицинская иммунология)
Osteomyelitis is an inflammation of bone and bone marrow caused by the spread of S. aureus from a local focus by the hematogenous route or from an open traumatic fracture; it is difficult to treat and remains a serious problem. The condition for spreading of the infectious process into bone is the effect of S. aureus and its impaired elimination due to immune system (IS) dysfunction. Controversial information on the immunopathogenetic mechanisms of acute osteomyelitis needs study, which would allow the development of sound immunotherapy. Purpose of the study: to specify the variants of antibacterial immune protection disorders in children with acute hematogenous and acute posttraumatic osteomyelitis. Materials and methods. Children 8-15 years old (n = 22) were studied: Study Group 1 (SG1, n = 12) – with acute hematogenous osteomyelitis (AHO); Study Group 2 (SG2, n = 10) – with acute post-traumatic osteomyelitis (APTO). The comparison group (CG) – 13 healthy children. Tested: Tlymphocytes (CD3+CD19- , CD3+CD4+, CD3+CD8+), B lymphocytes (CD3- CD19+), NK (CD3- CD16+CD56+) and TNK (CD3+CD16+CD56+) lymphocytes, neutrophil granulocytes (NG, CD16, CD32, CD64) (FC-500 Beckman Coulter, USA); the level of serum IgA, IgM, IgG (ELISA). Phagocytic function of NGs in relation to S. aureus was assessed: the number of actively phagocytizing NGs (%PhAN), capture processes (PhN, PhI) and killing activity (%D, DI). Results. In both groups was revealed a decrease of T lymphocytes, T helpers, TCTL and NK quantity (p1-4 < 0.05). In AHO, the levels of IgA, IgM, IgG did not differ from that in GS, while in APTO the levels of IgA and IgG increased (p1, 2 < 0.05). The density of CD64, CD16, CD32 receptor expression on NG in the studied groups has been a different equipping, predetermining an incompetence of the phagocytic function: in AHO associated with abnormalities in the function capture and killing, in APTO only with the S. aureus digestion. Conclusion. The revealed combined defects of IS functioning necessitate the development of new approaches in the treatment of AHO and APTO in children, pathogenetically substantiating the use of immunotherapy in the complex etiopathogenetic treatment. This approach will contribute to the restoration of mechanisms of anti-infective immunity, timely elimination of pathogens, improve the clinical course of the diseases, prevent the chronic inflammatory process.